EMERGING BUSINESS PARADIGMS TRANSITION FROM INDUSTRY 4.0 TO INDUSTRY 5.0 IN INDIA (CAHIERS MAGELLANES-NS, 2024)
This research paper delves into the unique Indian perspective on this transformation, exploring the challenges, opportunities, and implications it holds for businesses, policymakers, and researchers. The research is based on secondary data; published research papers on IR 4.0 and 5.0 from various journals, magazines, and reports from various consulting firms are gathered and reviewed to understand the research content and findings of various researchers worldwide. Data on Industry 4.0 is collected from official studies conducted by consulting firms, whilst data on policy is derived from published papers by the Indian government. Drawing upon a comprehensive review of literature, surveys, and expert interviews, this study investigates the multifaceted dimensions of Industry 5.0 in the Indian context. The findings shed light on how Industry 5.0 principles, emphasizing human-machine collaboration and customer-centricity, are impacting diverse sectors within India. The study also underscores the pivotal role of government policies and innovation ecosystems in facilitating this transition.